Partisipasi Pemberdayaan dan Kesejahteraan Keluarga (PKK) Desa Melalui Media Edukasi Digital untuk Mencegah Perkawinan Anak - Serah, Yenny Aman; Sirait, Resmaya Agnesia Mutiara; Jesajas, Thea Geneveva Josephine; Nugraha, Adhytia; Marpaung, Samuel (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2025)
Child marriage continues to be a significant issue in various Indonesian villages, including Lingkonong Village in Landak Regency. This issue has threatened children's education and health while obstructing the realization of their rights as the future generation of the nation. The Village Family Empowerment and Welfare Movement Team (TP-PKK) serves as an innovator by employing a community empowerment approach to address this issue. This community service initiative aims to enhance public legal awareness regarding the dangers of child marriage, while simultaneously equipping TP-PKK members with skills in utilizing digital media as a tool for prevention campaigns, particularly within the framework of the CEPAK (Child Marriage Prevention) Movement program. The Participatory Action Research (PAR) method is utilized, engaging TP-PKK members and residents in the design, implementation, and evaluation of educational programs. The primary activities encompass legal counseling, training in the utilization of digital platforms, the development of context-specific educational materials, and the dissemination of information via online media. The capacity of TP-PKK Lingkonong Village to manage digital campaigns promoting the CEPAK Movement has significantly increased. Their role as agents of change was effectively reinforced through the initiation of the campaign entitled "Lingkonong Village Towards a Generation Free of Child Marriage." This collaboration enables the community to comprehend the adverse effects of early marriage while also engaging in preventive initiatives. Digital media serves as an effective strategy for enhancing outreach, promoting collective awareness, and establishing a community environment that is more attuned to the safeguarding of children's rights